2002
DOI: 10.1590/s1517-74912002000300007
|View full text |Cite
|
Sign up to set email alerts
|

Efeito genotóxico do etanol em células da mucosa bucal

Abstract: RESUMO:O etanol é um dos agentes químicos relacionados ao desenvolvimento de neoplasias malignas bucais. Os micronúcleos são porções de cromatina que permanecem próximas ao núcleo, resultantes de mitoses aberrantes após a ação de agentes genotóxicos. Dessa forma, sua ocorrência reflete o grau de exposição celular a carcinógenos. O objetivo deste trabalho foi avaliar a freqüência de micronúcleos em células esfoliadas da língua e da mucosa jugal de indiví-duos dependentes químicos de etanol. A amostra constou de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
3
9
1
14
Order By: Relevance
“…The high frequency of MN observed in a group of patients studied was not influenced by gender and/or lifestyle factors such as cigarette smoking, alcohol consumption or the use of medications, in agreement with other investigators [33,34], although other studies have shown MN frequency associated with age [35] and exposure to chemical agents, tobacco and alcohol [36,37]. …”
Section: Discussionsupporting
confidence: 90%
“…The high frequency of MN observed in a group of patients studied was not influenced by gender and/or lifestyle factors such as cigarette smoking, alcohol consumption or the use of medications, in agreement with other investigators [33,34], although other studies have shown MN frequency associated with age [35] and exposure to chemical agents, tobacco and alcohol [36,37]. …”
Section: Discussionsupporting
confidence: 90%
“…A cocaína pode estar associada à aparição de lesões bucais, e pode ser administrada de várias formas, como inalada, fumada e até esfregada na gengiva (REIS et al, 2002;LINS et al, 2010;CHAIBEN, 2011). O Tabela 1 abaixo, apresenta as principais lesões bucais segundo a forma de administração da cocaína (REIS et al, 2002;LINS et al, 2010;CHAIBEN, 2011 ROCHA; MELO, 2013;FALCÃO et al, 2015).…”
Section: Saúde Bucal E O Usuário De Cocaínaunclassified
“…O Tabela 1 abaixo, apresenta as principais lesões bucais segundo a forma de administração da cocaína (REIS et al, 2002;LINS et al, 2010;CHAIBEN, 2011 ROCHA; MELO, 2013;FALCÃO et al, 2015).…”
Section: Saúde Bucal E O Usuário De Cocaínaunclassified
“…[35][36][37] In addition, a significant increase in the number of MN in lymphocytes of alcoholics compared with abstinent alcoholics and nonalcoholics has been reported. 38 There are also reports of higher frequency of cells in karyorrhexis in alcoholics.…”
Section: Dna Damages In Mexican Nativesmentioning
confidence: 99%